Uma leitura benjaminiana de experência em Graciliano Ramos: São Bernardo - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The present work examines the concept of “experience” according to German philosopher Walter Benjamin and the way it may contribute to the analysis of Graciliano Ramo’book, São Bernardo . The research aims to prospect the experiences that Paulo Honório, fir st person narrator, ambitioned to construct from his autobiographical lore for, then, to justify his personality and his feeling of property, submitting himself and other to the “destruction of self and the other”. Furthermore, we sinalize Paulo Honório as a prototype of the countryman, coated with rural characteristics bind to earth and that ennoble the rural life. Actually, he uses such characteristics to protect his disguise as predator of nature and of his subordinates. Thus, we will proceed with an ana lysis of the memories that constitute the hero’s subjectivity, to unveil the layers of the hard covering the life of this man who works on the dry earth has. Besides that, we will briefly touch the book Angústia (1974) to problematize our analysis. Lastly, it will be investigated the conflict of the man who aims at a project, justifying its advancement at the expanse of the reification of nature and of personal relations, impoverishing his experience, that should be inheritable.
Keywords: Walter Benjamin; Graciliano Ramos; Experiência; Walter Benjamin; Graciliano Ramos; Experience; CNPQ::LINGUISTICA, LETRAS E ARTES